Return to work after stroke: recording, measuring, and describing occupational therapy intervention - Grant, Mary; Radford, Kathryn; Sinclair, Emma; Walker, Marion (SAGE Publications, 2014)
Introduction: Existing research on vocational rehabilitation following stroke has been criticised for not describing intervention in sufficient detail for replication or clinical implementation. The purpose of this study was to test the feasibility of recording and measuring the content of an early stroke-specific vocational rehabilitation intervention delivered to participants in a feasibility randomized controlled trial, using a proforma previously developed for a study of vocational rehabilitation following traumatic brain injury. Method: The proforma was adapted for use in stroke with input from an expert panel and was used to record intervention content, in 10-minute units, following each intervention session. Findings: Twenty-five people, working or in education at the time of stroke, participated in the study. Two thirds of the therapists' time was spent in face-to-face contact (43%) and liaison with the patient and others (20%). Intervention mainly focused on work preparation (21%) and the return to work process (24%). The remaining time was consumed by administration (19%) and travel (18%). Conclusion: The proforma was quick and easy to use and captured the main focus of intervention. This study suggests that it can be used to record stroke-specific vocational rehabilitation intervention content and has potential for wider use in research and clinical practice.